Model datasets of orographical perturbation experiments for the Mongolian plateau by using CAS FGOALS-f3-L - Nuo Xu; Bian He; Zuowei Xie; Zhongda Lin; Shijian Feng; Yimin Liu; Guoxiong Wu; Qing Bao; Kangjun Chen; Natalia Victorovna Vazaeva; Shibo Gao (Scientific Data)
Abstract Topography is an important forcing for climate change. Compared to the extensively studies of Tibetan Plateau, the impact of Mongolian Plateau (MP) is less understood. This paper introduces three experiments which examine both the thermal and dynamical effects of the MP and its surrounding areas carried out by the climate model CAS FGOALS-f3-L. Each experiment produces 42 variables, including monthly, daily average, 6-hourly transient, and hourly outputs for precipitation and surface air temperature. The model datasets are all interpolated into nominal 1 degree resolution. The validation results show that the control run can well capture the basic circulation pattern over Eurasian continent, while the model responses to thermal and dynamical perturbations of MP are reasonable. These datasets provide a reference for understanding the response of weather and climate change in the middle and high latitudes to the mechanical and thermal forcing of the MP, and help to understand the contribution of the MP to the monsoon circulation, winter cold waves and even extreme events in the middle and high latitudes.